Le sujet sous l’angle de l’éducation à la biodiversité : perspectives d’un apprentissage selon trois dimensions - Serge Franc (Éducation et Socialisation)
In French ministerial guidelines, biodiversity in primary school is linked to both the sustainable development and the scientific topics. The official primary school program enjoins that expected learnings in this field are primarily cognitive and behavioral, while the affective dimension is minimized. In this context, the learner is often subjected to an essentially cognitive approach and develops an expected behavior. However, numerous studies show the significance of the affective dimension which interacts with the cognitive and behavioral dimensions in learning, and contributes to develop a critical point of view and a responsible behavior. Thus a subject actor and author could build his identity in a complex educative way, at the confluence of three dimensions of learning : knowledge, emotional maturity and behavior. Backed to a conceptual framework built on the analysis of these three dimensions, an experimental research on 285 students, aged 8 to 12 years, sheds light on the question : how a tridimentionality of learning could contribute to educate a subject to biodiversity ? The context of this research is based on the biodiversity of arthropods. The results show that there exist significant correlations between knowledge, emotional maturity and behavior. Taking into account these interactions could help to build a conscious, responsible and autonomous subject.